The mythologems of geopolitical conflicts - Zivkovic, Predrag; Samardžić, Obrad (Sociološki pregled, 2026)
To dispel the Dionysian narrative unease or the doubt about the epistemology of the paper, we will say that the authors’ statement contained in this multi-layered descriptor represents not only a sociological and philosophical but also a psychoanalytical interpretation of regional conflicts, whose mythological aspect has succeeded in gathering “the historical actors” and uniting them in the rehabilitation of their “geopolitical legacies” not only with political panaceas for the salvation of “democratic spirit” but, much more complex, with mythologem-like encounters. Here, we can recognize the influence of Carl Gustav Jung and Karl Kerenyi, whose mythological heritage will help us analyse the contemporary “geopolitical awakenings”, as Aleksandr Dugin would phenomenologically conclude. Referring to the aforementioned towering duo, sometimes “the sepulchral mythologem” is more important in the description of geopolitical forces, i.e., social battlefields, than any anticipated and daily informed calmness or. rather, geopolitical ambiguity because “the religious revolt”, which is considered the ruler of both regional and global conflicts, is kept in that archetypal structure. Through a chrestomathy of regional conflicts with a selection of archetypal examples of both the post-Soviet and Middle Eastern regions, we will try to explain their archetypal and geopolitical predictors.